A blueprint for cancer screening and early detection: Advancing screening's contribution to cancer control. (19th November 2018) - Wender, Richard C.; Brawley, Otis W.; Fedewa, Stacey A.; Gansler, Ted; Smith, Robert A.
Abstract: From the mid‐20th century, accumulating evidence has supported the introduction of screening for cancers of the cervix, breast, colon and rectum, prostate (via shared decisions), and lung. The opportunity to detect and treat precursor lesions and invasive disease at a more favorable stage has contributed substantially to reduced incidence, morbidity, and mortality. However, as new discoveries portend advancements in technology and risk‐based screening, we fail to fulfill the greatest potential of the existing technology, in terms of both full access among the target population and the delivery of state‐of‐the art care at each crucial step in the cascade of events that characterize successful cancer screening. There also is insufficient commitment to invest in the development of new technologies, incentivize the development of new ideas, and rapidly evaluate promising new technology. In this report, the authors summarize the status of cancer screening and propose a blueprint for the nation to further advance the contribution of screening to cancer control.